Request for decoration material supply for prototype room of PT2 at GF - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the request for decoration material supply for prototype room of PT2 at GF of BRACU new campus project.